Galectin-3 as a Therapeutic Target for NSAID-Induced Intestinal Ulcers - Park, Ah-Mee; Khadka, Sundar; Sato, Fumitaka; Omura, Seiichi; Fujita, Mitsugu; Hsu, Daniel K.; Liu, Fu-Tong; Tsunoda, Ikuo (Frontiers in Immunology, 2020)
Nonsteroidal anti-inflammatory drugs (NSAIDs) induce ulcers in the gastrointestinal tract, including the stomach and small intestine. NSAID-induced gastric ulcers can be prevented by taking acid-neutralizing/inhibitory drugs and cytoprotective agents. In contrast, there are no medicines to control NSAID-induced small intestinal ulcers, which are accompanied by a mucosal invasion of bacteria and subsequent activation of immune cells. Galectin-3 (Gal3), an endogenous lectin, has anti-microbial and pro-inflammatory functions. In the small intestine, since Gal3 is highly expressed in epithelial cells constitutively and macrophages inducibly, the Gal3 level can affect microbiota composition and macrophage activation. We hypothesized that the modulation of Gal3 expression could be beneficial in NSAID-induced intestinal ulcers. Using Gal3 knockout (Gal3KO) mice, we determined whether Gal3 could be a therapeutic target in NSAID-induced intestinal ulcers. Following the administration of indomethacin, an NSAID, we found that small intestinal ulcers were less severe in Gal3KO mice than in wild-type (WT) mice. We also found that the composition of intestinal microbiota was different between WT and Gal3KO mice and that bactericidal antibiotic polymyxin B treatment significantly suppressed NSAID-induced ulcers. Furthermore, clodronate, a macrophage modulator, attenuated NSAID-induced ulcers. Therefore, Gal3 could be an exacerbating factor in NSAID-induced intestinal ulcers by affecting the intestinal microbiota population and macrophage activity. Inhibition of Gal3 may be a therapeutic strategy in NSAID-induced intestinal ulcers.